Periventricular leucomalacia in premature infants in neonatal ward, Cipto Mangunkusumo Hospital: A preliminary study - Kemas Firman; Idham Amir; Nia Kurniati; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2004)
Introduction Periventricular leucomalacia (PVL) is a major causeof neurodevelopment delay in premature infants, so early detec-tion of the preterm infant at high risk for the subsequent develop-ment of this lesion is critical.Objectives To determine the prevalence of PVL in premature in-fants hospitalized in neonatal ward, Cipto Mangunkusumo Hospi-tal using cranial ultrasound scans and define its characteristicsMethods Premature infants hospitalized in the neonatal ward fromJanuary to July 2003 were included in this study. Clinical featureswere retrieved from medical charts. Ultrasound scan was performedonce, after the age of 7 days and interpretations were read sepa-rately by two consultants of the radiology division.Results Fifty-one infants were included, 21 with <32-week gesta-tion, 30 with >32-week gestation; birth weight range were 1000 to2600 gram. Nineteen infants had cystic lesion and/or dilatation ofthe ventricle from the cranial ultrasound scan. The prevalence ofPVL in gestational age (GA) of <32 weeks was 6/21 and that in GAof >32 weeks was 13/30. Risk factors found in infants with PVLwere maternal infection, respiratory distress, sepsis and circula-tory failure.Conclusion The prevalence of PVL in preterm infants in CiptoMangunkusumo neonatal ward was higher than that was reportedin developed countries. Maternal infection, respiratory distress,sepsis, and circulatory failure which were commonly found in theseinfants were factors to be considered as risks for PVL